rs-6r+st-6t=

Simple and best practice solution for rs-6r+st-6t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for rs-6r+st-6t= equation:


Simplifying
rs + -6r + st + -6t = 0

Reorder the terms:
-6r + rs + st + -6t = 0

Solving
-6r + rs + st + -6t = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-1st' to each side of the equation.
-6r + rs + st + -1st + -6t = 0 + -1st

Combine like terms: st + -1st = 0
-6r + rs + 0 + -6t = 0 + -1st
-6r + rs + -6t = 0 + -1st
Remove the zero:
-6r + rs + -6t = -1st

Add '6t' to each side of the equation.
-6r + rs + -6t + 6t = -1st + 6t

Combine like terms: -6t + 6t = 0
-6r + rs + 0 = -1st + 6t
-6r + rs = -1st + 6t

Reorder the terms:
-6r + rs + st + -6t = -1st + st + 6t + -6t

Combine like terms: -1st + st = 0
-6r + rs + st + -6t = 0 + 6t + -6t
-6r + rs + st + -6t = 6t + -6t

Combine like terms: 6t + -6t = 0
-6r + rs + st + -6t = 0

The solution to this equation could not be determined.

See similar equations:

| y=2x+6(6*7) | | 0=3y^2+30y+70 | | 5(n+2r)+3n= | | 0.3+0.6=1.5 | | 5x-3-2x=x+11 | | 2(3x-1)=8x+11 | | What*12=400 | | 5=v-2 | | 7x/6-3=25 | | Bp+25bp+p= | | 5(4+3x)+3=10 | | 5x=4x+17 | | 13x-1-8x+6= | | 7x-12=x+24 | | 6(5q+3w-2w)= | | 3(2n+10)= | | -2x-8=x+1 | | 5x-2=31 | | 3z-10=3-5(z+11) | | -9=-6(x-5) | | (x+5)+(3x-2)=280 | | -9=-6(x+5) | | 126+y=180 | | 4x-9+2x=-6x+5-3 | | 3*4+14-5-[-2]*7=-23 | | x+54=y | | -3k-1=12 | | x=3y(y+w)-1 | | k=5/8m | | 4x-9+2x=-6x+5 | | 6(3x+2)+5(7x-6)-12x=6(x-3)+5(6x-1) | | X^2-8x=100 |

Equations solver categories